Brainstem manifestations in neuromyelitis optica: a multicenter study of 258 patients. (June 2014) - Kremer, L; Mealy, M; Jacob, A; Nakashima, I; Cabre, P; Bigi, S; Paul, F; Jarius, S; Aktas, O; Elsone, L; Mutch, K; Levy, M; et al.
Background: Neuromyelitis optica (NMO) is a severe autoimmune disease of the central nervous system characterized by spinal cord and optic nerve involvement. Brainstem manifestations have recently been described. Objective: To evaluate the time of occurrence, the frequency and the characteristics of brainstem symptoms in a cohort of patients with NMO according to the ethnic background and the serologic status for anti-aquaporin-4 antibodies (AQP4-abs). Methods: We performed a multicenter study of 258 patients with NMO according to the 2006 Wingerchuk criteria and we evaluated prospectively the frequency, the date of onset and the duration of various brainstem signs in this population. Results: Brainstem signs were observed in 81 patients (31.4%). The most frequently observed signs were vomiting (33.1%), hiccups (22.3%), oculomotor dysfunction (19.8%), pruritus (12.4%), followed by hearing loss (2.5%), facial palsy (2.5%), vertigo or vestibular ataxia (1.7%), trigeminal neuralgia (2.5%) and other cranial nerve signs (3.3%). They were inaugural in 44 patients (54.3%). The prevalence was higher in the non-Caucasian population (36.6%) than in the Caucasian population (26%) ( p <0.05) and was higher in AQP4-ab-seropositive patients (32.7%) than in seronegative patients (26%) (not significant). Conclusions: This study confirms the high frequency of brainstem symptoms in NMO with a majority of vomiting and hiccups. The prevalence of these manifestations was higher in the non Caucasian population.